Identifying Causal, Contextual, and Intervening Factors Influencing the Likelihood of Financial Fraud in Companies - Mousakazemi , Seyyed Saeid; Ahmadi, Faegh; Ranjbar, Mohammad Hossein (Business, Marketing, and Finance Open, 2025)
Today, given the increasing need of managers for accurate financial information to make managerial decisions regarding the long-term prospects of companies, and the need to attract domestic and foreign investors for capital funding and competition in this domain, financial reporting has gained special importance. At times, financial reporting may fail to provide accurate information to stakeholders, which can result either from accountants' mistakes or from fraudulent reporting by managers. Fraudulent managerial reporting in financial statements poses a significant threat to investors. However, in practice, there is no immediate method to detect such fraudulent managerial reporting. Therefore, paying attention to direct indicators affecting the likelihood of fraud in financial reporting is essential. Accordingly, this study aimed to identify the causal, contextual, and intervening factors that influence the likelihood of financial fraud in companies listed on the Tehran Stock Exchange. The present research adopts a qualitative and exploratory approach. According to the research methodology, dimensions, components, and indicators affecting the likelihood of financial fraud in companies were first extracted through interviews. Using the Delphi method, eight dimensions and 39 indicators were identified and agreed upon by experts. The results of this study showed that the dimensions of weak earnings-based characteristics, weaknesses in financial reporting, weaknesses in board characteristics, weaknesses in internal controls, weaknesses in corporate governance systems, weaknesses in financial features, and corporate characteristics affect the likelihood of financial fraud in companies. These dimensions were derived through theoretical studies, synthesizing expert opinions in the field of accounting and auditing, analyzing the views of the statistical population, and gathering insights from specialists in related research domains.